Assessing Organizational Culture of Headquarters in Ministry of Health and Medical Education - Ali Ebraze; Fahimeh Rabbanikhah; Amir Kazemi-Bolboloy; Reza Moradi; Amin Aghili (Tehran University of Medical Sciences, 2019)
Background: Organizational culture is one of the important predictor of organizational effectiveness, and a key factor success of the organization as a competitive advantage. Todays, a continuous assessment of organizational culture status is considered essential; therefore, this study aimed to identify and measure organizational culture of the Ministry of Health and Medical Education. Materials and Methods: This descriptive-analytical study was conducted on the headquarters of the Ministry of Health and Medical Education in 2018. The study population consisted of all employees of the Ministry of Health and Medical Education (N=2200), 327 personals were selected through Cochran formula and stratified sampling method. The data collection instrument was a researcher-made questionnaire whose validity and reliability were confirmed (Cronbachchr('39')s alpha =86.5%). In order to data analysis SPSS24 using descriptive and inferential statistics tests were utilized. Results: The mean score of total organizational culture was 3.30 ± 0.70 from 5 which was higher than the theoretical average. Also, there was also a significant difference in partnership dimension in terms of employment type and in participation dimensions, accountability to the upstream institutions as well as total organizational culture score in terms of deputy. There was a direct statistical association between dimensions of organizational culture. Conclusion: According to study results, strong organizational culture will lead to improved performance in the organization and alignment of individuals and activities. Given the importance of specific role of culture in each organization, plans success and change strategies, human resources managers should take appropriate actions to improve internal and external communication and increase teamwork and accountability.